Penggunakan Enterprise Architecture Planning Pada Perencanaan Arsitektur Sistem Informasi Sekolah Di Smk Muhammadiyah Haurgeulis - Bisri, Muawan (KH. A. Wahab Hasbullah University, 2022)
Enterprise Architecture Planning (EAP) as one method or terms of reference for building an information architecture that is oriented to the needs of the business which consist of data architecture, application and technology as well as the plan to the implementation of the architecture that was created to support business activities for the achievement of the organization's mission. In the process of defining the architecture of the information, referring to a process that is common in the business organization of the education system, especially at SMK Muhammadiyah Haurgeulis Indramayu district, while the scope of the discussion surrounding the field of academic, financial management, personnel management or human resources and infrastructure.